2020
DOI: 10.1016/j.jvscit.2020.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical and surgical ablation of an anomalous upper extremity marginal vein in CLOVES syndrome identifies PIK3CA as the culprit gene mutation

Abstract: Anomalous marginal veins of the trunk or extremities are congenitally incompetent entities found in association with phosphatidylinositol 4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA)-related overgrowth syndromes, such as Klippel-Trénaunay syndrome and congenital lipomatous overgrowth, vascular malformations, epidermal nevi, and skeletal deformities (CLOVES) syndrome. When present, they can be a major source of venous hypertension-related morbidity and potentially lethal thromboembolic events. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Abnormal marginal veins (vein of Servelle/ lateral embryonal vein/ persistent embryonic vein) may be encountered both in Klippel-Trenaunay (KTS) and CLOVES syndromes and represent subdermal overgrowth of venous tissue, rather than signifying noninvoluting embryonic remnants. 44 Therefore, the term “anomalous marginal vein” has been suggested as a more appropriate nomenclature. 44 These phlebectasias may be detected in central, thoracic, cervical and extremity locations.…”
Section: Clinical Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abnormal marginal veins (vein of Servelle/ lateral embryonal vein/ persistent embryonic vein) may be encountered both in Klippel-Trenaunay (KTS) and CLOVES syndromes and represent subdermal overgrowth of venous tissue, rather than signifying noninvoluting embryonic remnants. 44 Therefore, the term “anomalous marginal vein” has been suggested as a more appropriate nomenclature. 44 These phlebectasias may be detected in central, thoracic, cervical and extremity locations.…”
Section: Clinical Findingsmentioning
confidence: 99%
“… 44 Therefore, the term “anomalous marginal vein” has been suggested as a more appropriate nomenclature. 44 These phlebectasias may be detected in central, thoracic, cervical and extremity locations. 2 , 3 , 17 , 36 , 44 , 45 Anomalous marginal veins possess a high risk of venous hypertension-related morbidity, deep vein thrombosis and potentially fatal pulmonary embolism.…”
Section: Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…After control of the outflow tracts, a mechanochemical ablation (MOCA) was performed using 3.5 mL of 1.5% STS with completion venography and duplex US confirming no residual flow through the lateral marginal vein. 61 The MOCA technique has a dual mechanism: a rotating wire tip provides mechanical damage to the endothelium and the sclerosing agent causes chemical damage. 62 In a prospective study of 13 MOCA procedures on 11 patients, Lambert et al demonstrated that primary occlusion without any adverse events were achieved by this technique with partial recanalization and symptom recurrence only occurring in 2 of 11 patients (18%) at 14- and 18-month follow-up.…”
Section: Molecular Therapiesmentioning
confidence: 99%